Transcriptomic analysis of the defense response in “Cabernet Sauvignon” grape leaf induced by Apolygus lucorum feeding - Heng Yao; Suhong Gao; Tianhua Sun; Guona Zhou; Changkuan Lu; Baojia Gao; Wenshu Chen; Yiming Liang (Plant Direct)
Abstract To investigate the molecular mechanism of the defense response of “Cabernet Sauvignon” grapes to feeding by Apolygus lucorum, high‐throughput sequencing technology was used to analyze the transcriptome of grape leaves under three different treatments: feeding by A. lucorum, puncture injury, and an untreated control. The research findings indicated that the differentially expressed genes were primarily enriched in three aspects: cellular composition, molecular function, and biological process. These genes were found to be involved in 42 metabolic pathways, particularly in plant hormone signaling metabolism, plant‐pathogen interaction, MAPK signaling pathway, and other metabolic pathways associated with plant‐induced insect resistance. Feeding by A. lucorum stimulated and upregulated a significant number of genes related to jasmonic acid and calcium ion pathways, suggesting their crucial role in the defense molecular mechanism of “Cabernet Sauvignon” grapes. The consistency between the gene expression and transcriptome sequencing results further supports these findings. This study provides a reference for the further exploration of the defense response in “Cabernet Sauvignon” grapes by elucidating the expression of relevant genes during feeding by A. lucorum.